Bahasa Inggris - Zukya Rona Islami; Fadhil Sidiq; Rizkei Kurniawan (Postgraduate, University of Mataram, 2023)
Sensitivity to the environment is an ability that must be possessed by students to be able to find alternative solutions that are right for solving environmental problems. Therefore, the study aims to develop a SETS-based environmental geography textbook using the ADDIE development model and environmental geography course students as respondents. Data was collected using validation sheets and FGD narratives by experts to maintain textbook quality and descriptive analysis. Using a geographical approach, environmental geography textbooks were developed on the basis of SETS. The textbook contains topic sub-chapters, illustrations in tables and graphs, assignments, and activity-based exercises. Based on SETS, practical steps are used to develop environmental geography textbooks, including presenting contextual science materials; presenting local, national, and international environmental issues; presenting examples of the use of technology in overcoming environmental problems;Â describing the impact of technology use on the environment and society; and designing evaluations of problem-based textbooks with student activities including SETS elements and involving a geographic approach. This textbook is intended to be used by lecturers of Indonesian environmental geography and subsequent studies as reference material.